Synthesis and polymerization of 1-(2-diallylaminoethyl) pyrimidines - Elaridi, Jomana (2018)
We report the preparation and characterization of three pyrimidine-based monomers, specifically: 1-(2-diallylaminoethyl)uracil, 1-(2-diallylaminoethyl)thymine and 1-(2-diallylaminoethyl)cytosine. Monomer synthesis was initiated by reaction of the pyrimidine with ethylene carbonate to form the hydroxyethyl adduct which was subsequently chlorinated to afford the chloroethyl intermediate. Reaction of the chloroethyl derivatives with diallylamine resulted in the desired monomers. We demonstrated a two-fold increase in the overall yield of the three monomers in comparison to reported procedures. The cyclopolymerization and cyclo-copolymerization of 1-(2-diallylaminoethyl)pyrimidine trifluoroacetate salts in water resulted in low-yield homopolymers. In contrast, the neutral 1-(2-diallylaminoethyl)pyrimidines cyclo-copolymerized with sulfur dioxide and V-50 initiator to yield the corresponding copolymers in higher yields ranging from 30 to 60%.